2022
DOI: 10.1002/mbo3.1260
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antibiotics on the human microbiome and consequences for host health

Abstract: It is well established that the gut microbiota plays an important role in host health and is perturbed by several factors including antibiotics. Antibiotic‐induced changes in microbial composition can have a negative impact on host health including reduced microbial diversity, changes in functional attributes of the microbiota, formation, and selection of antibiotic‐resistant strains making hosts more susceptible to infection with pathogens such as Clostridioides difficile. Antibiotic resistance is a global cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(205 citation statements)
references
References 279 publications
(345 reference statements)
3
134
1
2
Order By: Relevance
“…Studies indicate that socioeconomic status may alter oral microbiota community structure and higher diversity ( 132 , 133 ). The oral microbiota is a major reservoir of antibiotic-resistant bacteria; many studies have demonstrated that using amoxicillin, erythromycin, and tetracycline changes oral microbiota composition and enriches bacteria resistant to antibiotics ( 134 , 135 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies indicate that socioeconomic status may alter oral microbiota community structure and higher diversity ( 132 , 133 ). The oral microbiota is a major reservoir of antibiotic-resistant bacteria; many studies have demonstrated that using amoxicillin, erythromycin, and tetracycline changes oral microbiota composition and enriches bacteria resistant to antibiotics ( 134 , 135 ).…”
Section: Resultsmentioning
confidence: 99%
“…The imbalance of gut microbiomes (beneficial and pathogenic) alter the immune interactions, which cause autoimmune diseases, including gastrointestinal disorders (inflammatory bowel disease and celiac diseases), rheumatic arthritis, malignancy, neurodegenerative disorders, and metabolic syndrome [ 5 , 6 , 7 , 8 , 9 , 10 ]. Food habits, overuse of antibiotics, and unique genetic characteristics of hosts could alter the gut microbiome [ 11 , 12 ]. Studies have suggested that probiotic supplementation can improve host gut health and prevent auto-immune-related inflammatory diseases [ 1 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Side-effects of antimicrobials: Antimicrobials are designed to specifically target to pathogens, but off-target or side-effects are very common. For instance, antibiotics not only inhibit pathogenic bacteria, but also intoxicate patients' internal organs, such as liver and kidney 18,19 , as well as disrupt the microbiota in the gastric intestinal tract 20 ; Some antivirals have a poor specificity of distinguishing viral targets from host molecules 21 . Most antifungals and antiparasitic drugs are toxic to human cells because eukaryotic cells share significant similarity 22 .…”
Section: Significance Of the Hpi-equation In Shifting The Paradigm Of...mentioning
confidence: 99%